2012
DOI: 10.1136/gutjnl-2011-301857
|View full text |Cite
|
Sign up to set email alerts
|

NKT-associated hedgehog and osteopontin drive fibrogenesis in non-alcoholic fatty liver disease

Abstract: Immune responses are important in dictating nonalcoholic steatohepatitis (NASH) outcome. We previously reported that upregulation of hedgehog (Hh) and osteopontin (OPN) occurs in NASH, that Hh-regulated accumulation of natural killer T (NKT) cells promotes hepatic stellate cell (HSC) activation, and that cirrhotic livers harbor large numbers of NKT cells. Here, we evaluated the hypothesis that activated NKT cells drive fibrogenesis during NASH by assessing if NKT depletion protects against NASH-fibrosis; ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
181
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(200 citation statements)
references
References 38 publications
14
181
1
1
Order By: Relevance
“…Prior studies have suggested hepatic endothelium as the major source of CXCL16 in the liver in homeostasis (15), and cholangiocyte-derived CXCL16, secreted following Hedgehogpathway-dependent crosstalk with HSC, as a strong stimulus for NKT cell migration in injury (31,32). In our study, we could clearly demonstrate that also monocyte-derived inflammatory macrophages and resident Kupffer cells (defined as reported in Ref.…”
Section: Discussionsupporting
confidence: 74%
“…Prior studies have suggested hepatic endothelium as the major source of CXCL16 in the liver in homeostasis (15), and cholangiocyte-derived CXCL16, secreted following Hedgehogpathway-dependent crosstalk with HSC, as a strong stimulus for NKT cell migration in injury (31,32). In our study, we could clearly demonstrate that also monocyte-derived inflammatory macrophages and resident Kupffer cells (defined as reported in Ref.…”
Section: Discussionsupporting
confidence: 74%
“…OPN also delays liver fibrosis resolution due to sustained fibrillar collagen-I deposition in mice after thioacetamide-induced fibrosis [7] . Recently, plasma OPN levels have been found to predict liver fibrosis in various chronic liver diseases, such as NASH [11] , alcoholic liver disease [12] , and chronic viral hepatitis B [13] and C [14] . Pereira et al [21] have also demonstrated that OPN secretion could be stimulated by Schistosoma mansoni and that serum OPN levels correlated with splenic vein pressure and liver fibrosis stage in patients with schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, plasma OPN levels have been found to be significantly elevated in patients with liver cirrhosis and HCC compared to those without HCC [10] . Recently, plasma OPN levels were shown to predict liver fibrosis in various chronic liver diseases, such as non-alcoholic steatohepatitis [11] , alcoholic liver disease [12] , and chronic viral hepatitis B [13] and C [14] . As OPN levels correlate significantly with the fibrosis stage in alcohol-induced liver disease [12] , it follows that OPN levels could be related to the degree of portal hypertension and, hence, serve as a surrogate non-invasive marker of portal hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of infant fibrosis (biliary atresia, Caroli's disease, congenital hepatic fibrosis) and adult primary biliary cirrhosis (PBC), primary sclerosing cholangitis (PSC), and secondary biliary fibrosis, all liver diseases of other etiologies, once advanced, develop into a portal fibrosis with proliferation of biliary progenitors, especially when excessive hepatocyte apoptosis forces the stem cell niche to produce biliary progenitors. These biliary progenitors are more resistant to enhanced oxidative stress and hepatocyte death, such as induced by ASH, NASH, or severe post-transplant hepatitis C (55)(56)(57)(58)(59)(60). Drugs aimed at the biliary fibrogenic progenitors are effective antifibrotic agents in rodent biliary and advanced non-biliary fibrosis.…”
Section: Figurementioning
confidence: 99%